Agricultural Studies from the Perspective of Gender History in Indonesia and Gender Equality (Journal of Communication and Multidisciplinary studies, 2026)
This paper examines the historical development of gender relations in Indonesia and the ongoing struggle for gender equality from the pre-colonial period to the contemporary era. The study focuses on how social, cultural, political, and economic structures have shaped the roles and positions of women across different historical phases, including the pre-colonial era, colonial period, national independence, the New Order regime, and the post-Reformasi period. This research employs a qualitative descriptive approach using a literature study method. Data were collected from books, academic journals, official reports, and historical documents relevant to gender studies in Indonesia. The collected data were analyzed through thematic and historical analysis to identify patterns of continuity and change in gender relations. The findings reveal that gender roles in pre-colonial Indonesian societies were diverse and context-dependent, with some communities granting significant authority to women. Colonialism introduced rigid patriarchal structures that limited women’s public roles, while the nationalist movement reopened space for women’s participation. However, the New Order regime reinforced gender domestication through state ideology. The Reformasi era marked a turning point with the emergence of gender-responsive policies and women’s movements, although structural challenges such as patriarchy, gender-based violence, and unequal political representation persist. In conclusion, gender equality in Indonesia is a dynamic and ongoing process that requires sustained legal, educational, and social efforts to create a more just and inclusive society.